Obedience to authority, cognitive and affective responses and leadership style in relation to a non-normative order: the Milgram experiment - da Costa, Silvia (2021)
The influence of the context on behavioral and emotional reactions to a war crime situation military cadets (N = 315) is analyzed. The study is based on Milgram’s experience and the tragedy of My Lai.It examines personal and peer obedience to an anti-normative order (asking participants whether they would obey an order to shoot unarmed civilians) in five vignettes or scenarios that reproduce Milgram’s conditions and MyLai scenario. This is an experimental between-within study of five scenarios by two conditions (Milgram, 1974). Personal and collective obedience of other military, emotional reactions and values of Schwartz (2012) were measured. Showing enhancement of self-bias it is reported that the pairs would be more likely to shoot than one would. Replicating Milgrams’s results, obedience is greater when the order is given directly by an authority, and lower when there is conflict between authorities and peers rebel. Confirming that identification with humanity and not just with the in-group may prompt respondents to reject an anti-normative order, values of transcendence of the self are associated with less obedience and congruent emotional reactions. Self-perceived transformational leadership was associated with positive emotions towards peer that disobey to fire. However a transformational style perceived in the superior was associated to positive emotions by respect to soldier who open fire, adding information on the potential dark side of this leadership style. The relevance of personal values, leadership style and affectivity in military context is discussed.